Proposition and application of an environmental salubrity index in rural agglomerations - Débora de Lima Braga; Nolan Ribeiro Bezerra; Paulo Sérgio Scalize (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE Propose an Índice de salubridade ambiental (ISARural - environmental salubrity index) that expresses the conditions experienced in rural agglomerations, including indicators and subindicators for its subsequent application in rural communities in the state of Goiás. METHODS We developed the research in three phases: 1) previous analysis for the proposition of an ISARural, with the participation of seven specialists; 2) proposition of the ISARural by means of the Delphi method, starting with 168 specialists from 26 federative units of Brazil and Distrito Federal; and 3) application of the ISARural in 43 rural communities in the state of Goiás. RESULTS The proposed ISARural resulted in the composition of eight indicators, four of which related to basic sanitation, and the others to health, socioeconomic conditions, public services offered, and housing conditions. The weight assigned to each indicator ranged from 22.82% for the water supply indicator to 6.35% for the service indicator, it is possible to apply the ISARural fully or to evaluate each indicator individually. The application of ISARural in communities of Goiás classified 86% of them with low salubrity, highlighting the worst conditions for quilombola communities. The sanitary sewage had the lowest score among the ISARural indicators, requiring greater attention from public authorities. CONCLUSIONS This study contributed to the proposition of an index in line with the concept of environmental salubrity, useful in the scope of public policies as a conditioner for the prioritization of actions needed to improve the salubrity conditions identified. The proposed ISARural can be fully applied or used in the individual evaluation of each indicator of its composition. The results of its application made it possible to identify the communities with the worst environmental salubrity conditions and the indicators that require greater priority attention in the communities studied.